2018
DOI: 10.17269/s41997-018-0126-6
|View full text |Cite
|
Sign up to set email alerts
|

Drug checking at an electronic dance music festival during the public health overdose emergency in British Columbia

Abstract: Setting Shambhala is a 5-day electronic dance music (EDM) festival held in rural British Columbia that annually hosts between 15,000 and 18,000 people on a 500-acre ranch. The AIDS Network Outreach & Support Society (ANKORS) has provided harm reduction services throughout the duration of the festival since 2003, including point-of-care drug checking, which allows realtime testing of illicit substances to assess their composition. Drug checking results are provided directly to clients and displayed in aggregate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 3 publications
3
40
0
Order By: Relevance
“…While prior research has established that pill testing services are endorsed by people who have used MDMA in Australia and overseas , few studies have reported subsequent substance‐using decisions of MDMA users following a pill test result in a festival environment . Therefore, the present study offers an important contribution to a body of research supporting pill testing as a form of harm reduction at music festivals.…”
Section: Discussionmentioning
confidence: 85%
“…While prior research has established that pill testing services are endorsed by people who have used MDMA in Australia and overseas , few studies have reported subsequent substance‐using decisions of MDMA users following a pill test result in a festival environment . Therefore, the present study offers an important contribution to a body of research supporting pill testing as a form of harm reduction at music festivals.…”
Section: Discussionmentioning
confidence: 85%
“…Variations in services relate to the primary purpose of the testing; who conducts the analyses and how; the range of quantitative or qualitative analytical methods used; who disseminates test results and how; where testing is located (such as mobile/ event-based or fixed site/ community-based); whether test results go directly to users or via an intermediary; and the varying levels of engagement and support from other stakeholder groups. At the Canadian Shambhala festival, for example, test results are not shared directly between the testing service and other onsite agencies such as police (Michelow and Dowden, 2015). By comparison, Multi Agency Safety Testing (MAST), the term coined by the author for the model of drug safety testing piloted in the UK (Measham, 2016), is distinctive in that firstly, it foregrounds the sharing of test results with onsite and offsite stakeholders with the agreed aim of reducing drug-related harm and secondly, test results are delivered by healthcare staff embedded in brief interventions (Fisher and Measham, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…At micro–level, disposal of unwanted substances has been utilised as a key indicator of impact on individual service users, in part due to the relative ease of measuring disposals by comparison with other outcomes, the potential for comparison between testing services, and the indisputable benefit (apparent even to critics) of taking substances of concern out of circulation. Testing services worldwide report that a significant proportion of service users intend not to take further substances in their possession after service delivery, particularly if test results suggest that contents were adulterated, missold or otherwise other than expected …”
Section: Drug Safety Testingmentioning
confidence: 99%
“…worldwide report that a significant proportion of service users intend not to take further substances in their possession after service delivery, particularly if test results suggest that contents were adulterated, missold or otherwise other than expected. [24][25][26][27][28][29][30][31][32] Drug safety testing disposal rates vary widely depending on composition profiles and adulteration rates identified by forensic analyses, with a review 33 suggesting that disposal rates for testing services ranged from 4-76% and subsequent studies suggesting that the range is even wider. Furthermore, distinctions have been made between intended disposals, 34,35 actual disposals to a testing service, 29 and verified disposals to an external agency.…”
Section: What This Study Addsmentioning
confidence: 99%